2012
DOI: 10.1159/000339706
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Hypoxia-Inducible Factor-1α in Gastrocnemius Muscle in Rats with Chronic Kidney Disease

Abstract: Background/Aims: Hypoxia-inducible factor (HIF)-1α is responsible for increased expression of genes engaged in angiogenesis. Our previous study indicated capillary rarefaction and atrophy of glycolytic fibers, mainly in locomotor muscles of uremic animals. Perhaps these changes are secondary to disturbances of HIF-1α in skeletal muscles. Methods: Expression of HIF-1α at mRNA and protein levels, as well as mRNA of vascular endothelial growth factor A (VEGF-A), vascular endothelial growth factor receptor (VEGFR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 77 publications
5
23
1
Order By: Relevance
“…These discrepancies might indicate 1) an altered response to hypoxia at the muscle fiber level in the course of the uremic myopathy and 2) that changes seen in fiber-type composition, oxidative and glycolytic enzymes, and fiber size in Nx animals were not induced by high levels of HIF-1␣. The higher expression of HIF-1␣ protein seen in the present study in the fast vs. the slow muscles is in agreement with previous results in rat control muscles (15,25,29), and confirms that HIF-1␣ may play a role in maintaining normal properties in fast muscles (25). The reduced expression of HIF-1␣ protein found in our study in the fast tibialis cranialis muscle, but not in the slow soleus muscle from Nx rats, is not a new finding (15), indicating that postural muscles seem to be more resistant to hypoxia and muscle changes secondary to uremia than locomotor muscles.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…These discrepancies might indicate 1) an altered response to hypoxia at the muscle fiber level in the course of the uremic myopathy and 2) that changes seen in fiber-type composition, oxidative and glycolytic enzymes, and fiber size in Nx animals were not induced by high levels of HIF-1␣. The higher expression of HIF-1␣ protein seen in the present study in the fast vs. the slow muscles is in agreement with previous results in rat control muscles (15,25,29), and confirms that HIF-1␣ may play a role in maintaining normal properties in fast muscles (25). The reduced expression of HIF-1␣ protein found in our study in the fast tibialis cranialis muscle, but not in the slow soleus muscle from Nx rats, is not a new finding (15), indicating that postural muscles seem to be more resistant to hypoxia and muscle changes secondary to uremia than locomotor muscles.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, previous studies in short-term animal models of uremia have reported a different impact on skeletal muscles with different functional competences (15)(16)(17). For example, the fiber atrophy of fast-twitch fibers and capillary rarefaction that occur in rats in early stages (4 wk) of CRF was noted to be more severe in limb (gastrocnemius) than in trunk (longissimus thoracis) muscles (15)(16)(17).…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, VEGF-A mRNA and protein levels were reduced in HFD-fed UniNx compared with sham-operated mice, suggesting that reduced HIF-1a may be responsible for reduced capillary density in the former. Importantly, UniNx and subtotal nephrectomy in Wistar rats were associated with reduced expression of HIF-1a, VEGF-A, and VEGF receptor in gastrocnemius muscle (44). In addition, subtotal nephrectomy reduced skeletal muscle angiogenesis in rats (45).…”
Section: Discussionmentioning
confidence: 99%